Impact of practitioner's training in the management of alcohol dependence: a quasi-experimental 18-month follow-up study - Reynaud Michel; Malet Laurent; Llorca Pierre-Michel; Falissard Bruno (BMC, 2006)
Abstract Background In many European countries, medical education on alcohol remains inadequate in terms of both quantity and quality. The expansion of GP training and care protocols would improve the management and outcome of alcoholic patients. Our purpose was to assess the impact of a multifaceted intervention by trained GPs in the management of alcohol-dependent patients. Results and discussion Trained GPs proved better i) in the attempt at abstinence, with 67% patients becoming sober vs. 47% in a comparison sample and ii) in repeat attempt at abstinence in the event of relapse, with an average 2.99 vs. 1.31 attempts per patient. There were no differences in terms of i) relapses, which involved about three in four patients, and ii) prolonged abstinence, which averaged two months. Overall, patients managed by trained GPs remained abstinent 103 days during the 18-month follow-up period vs 68 days for the comparison sample (p = 0.016). Methods This 18-month follow-up study had a quasi-experimental design with 24 volunteer trained GPs and a comparison sample of a representative sample of 24 GPs. All GPs included their own already existing DSM-IV alcohol-dependent patients. Patients with depression or anxiety comorbidities were included. Participants were 126 patients in the trained sample and 122 in the comparison sample. The two patient samples were evenly-balanced, averaging 47 years old and 80% males. In the trained sample, consultations were scheduled and management (medication, biological workup) was protocolized, whereas the comparison sample representing standard practice had no obligations. Conclusion Medical education can sharply improve the management of alcohol-dependent patients and short-term outcome. Trained GPs lead more patients to attempt abstinence and more often than in standard practice. However, a strict medical approach remains limited in the maintenance of medium-term abstinence (over two months), providing a strong argument for multidisciplinary management of alcohol-dependent patients.